Suitable climate for rubber trees affected by the South American Leaf Blight (SALB): Example for identification of escape zones in the Colombian middle Magdalena - Jaimes, Yeirme [UNESP]; Rojas, Jairo; Cilas, Christian; Furtado, Edson L. [UNESP] (Elsevier B.V., 2016)
South American Leaf Blight (SALB), caused by the fungus Pseudocercospora ulei, is the major constraint for rubber tree cultivation in Latin America, continent of origin of the rubber tree. The use of resistant tree cultivars and the identification of escape zones seem to be the best disease control measures. In order to characterize the climate and the pedological parameters in the region of Middle Magdalena, Colombia, we used temperature, relative humidity and annual rainfall records for a 20-year period (1990-2010) from 19 weather stations distributed across the region, together with definitions of the soil units for the area. With the recorded data, we calculated annual and monthly averages of temperature and relative humidity, annual rainfall, annual water balance, annual potential evapotranspiration, number of months with rainfall lower than 50 mm and 100 mm, and number of months with relative humidity lower than 75%. To determine the suitable climate for the rubber crop facing SALB, these results were interpolated through Inverse Distance Weighting with the software ArcGis 9.3 for each variable and their combinations, having as references the plant requirements and the disease escape areas. Regarding the annual rubber tree evapotranspiration requirement, the map showed that the region of Middle Magdalena is suitable for the rubber cultivation. However, La Gloria (Cesar), Regidor (Bolivar) and Gamarra (Cesar) are not suitable for rubber cultivation owing to the high soil hydric deficit (>500 mm). When we considered the rubber tree's requirements, the region was divided into the following types of areas: two unsuitable, two marginal and one suitable. However, considering the disease escape requirements, this region was divided into one unrestricted area and six preferential areas with different restrictions to the SALB control. The most important area of the Middle Magdalena Region is not an escape zone, hence in these areas, the use of highly productive clones resistant to P. ulei is suggested. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Hevea brasiliensis; Pseudocercospora ulei; Zoning; Escape zones